Color Preference of Three Parasitoids Imported to the Americas for the Biological Control of the Coffee Berry Borer (Curculionidae: Scolytinae). Issue 3 (12th May 2020) - Castillo, Alfredo; Rojas, Julio C
Abstract: The African parasitoids Cephalonomia stephanoderis Waterston (Bethylidae: Hymenoptera), Prorops nasuta Betrem (Bethylidae: Hymenoptera), and Phymastichus coffea LaSalle (Eulophidae: Hymenoptera) are biological control agents of the coffee berry borer (Coleoptera: Curculionidae). In this study, we investigated in laboratory the female behavioral responses of these parasitoids to 14 different wavelengths (340–670 nm) against a control (570 nm, yellow). When nonchooser females were included in the analysis, none parasitoids species showed a preference between 340, 350, 370, 460, 490, 520, 540, 590, 640, and 650 nm with respect to the control wavelength. In contrast, the three species of parasitoids were more attracted to wavelengths of 380, 400, and 420 nm than the control wavelength. Phymastichus coffea and P . nasuta were more attracted to the wavelength of 400 and 420 nm compared to C . stephanoderis . At 380 nm, P . coffea and C . stephanoderis wasps showed the higher responses in comparison to P . nasuta females. When nonchooser wasps were excluded from the analysis, we observed other differences among the parasitoid species. For instance, P . coffea were more attracted to 490–540 nm than to 570 nm, whereas the bethylids did not discriminate between 490–540 nm or 570 nm. Our results are discussed in relation to possible implications associated with the vision of these parasitoid species.